Peran Literasi Keuangan, Risk Tolerance, Overconfidence Serta Financial Technology dalam Mendorong Keputusan Investasi - Kulintang, Amelia; Putri, Eskasari (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
This research explores the roles of financial literacy, risk tolerance, overconfidence, and financial technology in investment decision-making. The conceptual framework is grounded in prospect theory, particularly in the context of investment decisions. A quantitative research method using a questionnaire was employed to collect primary data from an active student sample of the Faculty of Economics and Business at Universitas Muhammadiyah Surakarta. A total of 110 participating students served as research respondents. The collected data were processed and analyzed descriptively and inferentially. The research results indicate that financial literacy, risk tolerance, overconfidence, and financial technology collectively play significant roles in influencing investment decisions. Among these factors, overconfidence was identified as the most influential at a dominance level. These findings have crucial implications for enhancing investors' understanding of the capital market, refining more precise investment strategies, and minimizing risks. Therefore, this research contributes to directing attention toward the aspects of financial and psychological literacy in investment decision-making, in conjunction with the advancements in financial technology.A better understanding of these variables can aid in optimizing investment decisions in the capital market, providing a foundation for the development of financial literacy programs, and adopting more effective approaches in managing investment risks.